Optically Controlled Microwave Attenuators - P. Bhushan Mital (Active and Passive Electronic Components)
The concept of photoconductivity is utilized in a number of microwave applications such as switches and attenuators. Optically controlled microwave attenuators prove an alternative to the conventional attenuators due to their simplicity, easy of operation, and very narrow ranges of continuously varying attenuation levels available. This paper describes the design of such configurations of optically controlled attenuators on a microstrip line fabricated on a semiconductor substrate.